Effect of Lecturer Certification Allowance, Lecturer Education, and Lecturer Training on Lecturer Performance - Sinarti Sinarti; Siti Rahmawati (Journal of Applied Accounting and Taxation, 2017)
This study examines the effect of the certification allowances lecturer, faculty of education, training and lecturer on the performance of the lecturer. This research was conducted using questionnaires to all samples certified lecturer. The data obtained were then processed using regression analysis. The number of questionnaires are processed totaled 75 questionnaire. Hypothesis test results have shown that the benefits of certification lecturers, professors of education, and training faculty positive and significant effect on the performance of the lecturer. Allowances for lecturers who have followed the certification, provide opportunities for continuing education for faculty, and provide training opportunities according to their field can improve the performance of lecturers. The samples in the study have not been evenly distributed and performance assessment are used in the form of self-appraisal, so that further research can be used to sample a wider and performance assessment is done by looking at Work Target Employees for lecturers Civil Servant and the achievement of academic rank private colleges.